Spittlebug impacts on sugarcane quality and ethanol production - Ravaneli, Gisele Cristina; Garcia, Débora Branquinho; Madaleno, Leonardo Lucas; Mutton, Miguel Ângelo; Stupiello, José Paulo; Mutton, Márcia Justino Rossini (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the impacts of spittlebug (Mahanarva fimbriolata) attack on sugarcane quality and ethanol production. Technological and microbiological parameters of juice and fermentation process were evaluated in ten fermentation cycles and two harvest seasons. Treatments consisted of different spittlebug stalk damage levels: control, with 100% of apparently healthy stalks; medium, with 15% of damaged or dry stalks (DDS); high, with 30% of DDS; and very high, with 60% of DDS. Spittlebug attack caused significant losses in cane quality, reducing total soluble solids, sucrose content, total reducing sugars, and pH, and increasing total phenolic compounds, and total and volatile juice acidity. The fermentation process was also significantly affected, resulting in lower ethanol content in wine. There was an increase in acetaldehyde concentration in the distillate. The spittlebug attack caused negative impacts on sugarcane quality and fermentation process, and these impacts are stronger in late season harvests.